(untitled) (Research, Society and Development, 2022)
In the last two decades, there has been a significant increase in studies in the area of ​​health on violence, mainly due to the recognition of it as a serious public health problem. Bearing this reality in mind, the objective of this work was to characterize the profile of notifications caused by physical violence during the period from 2016 to 2020 in the State of Pará. This study has a retrospective ecological character with a quantitative approach, using secondary data from the Notifiable Diseases Information System (NDIS) and Mortality Information System (MIS). The results of the study showed that 16,446 notifications of cases of physical violence were registered in Pará, from 2016 to 2020. It was observed that 23.25% (n=3,823) of the notifications were male and 76.73% ( n=12,619) to females. It was observed that most reports of physical violence in Pará occurred in brown people (73.95%), followed by white people (12.43%) and black people (8.69%). Thus, the results showed that women, browns and young people are more susceptible to physical violence, with the residence as the main place of occurrence. With regard to deaths from aggressive causes, males (92.69%) and brown people (85.39%) stood out. Therefore, the need to prepare health systems for the care and monitoring of victims is reinforced, including referrals to specific services, ensuring inclusion in lines of care and appropriate protection services for each individual.